(untitled) (e-Journal of Linguistics, 2025)
Nowadays, the development of technology is advancing rapidly, including in the field of communication. Social interaction has shifted to the digital sphere, with TikTok being one of the most popular social media platforms that allow users to interact without geographical restrictions. This development has triggered the emergence of neologisms and new linguistic features in social media interactions. Therefore, this study aims to explore the most common forms of neologism and linguistic forms that have emerged on the TikTok platforms and illuminate the impact of these phenomena on social discourse. It also highlights the role of social media as both a platform for expression and a driving force behind linguistic change. A qualitative approach with an observation method was applied in this research to deeply explore these issues. The findings reveal that the most common type of neologism is lexicographic, with a percentage of occurrence at 50%, while the use of emojis represents the most dominant new linguistic form on TikTok. These phenomena have impacted linguistic changes in social discourse, with the potential for new words to be added to modern dictionaries. Consequently, vocabulary continues to expand in line with the advancement of technology. In addition, this difference in languagechanges may lead to communication gaps among generations.